Comunicação e acessibilidade: inclusão social em bibliotecas públicas na era das tecnologias digitais - Cosmano, Sergio Roberto (2015)
The purpose of this Doctoral research is to investigate the relationships between the means of communication and the accessibility of the social inclusion process in public libraries in the age of digital technologies, and to analyze the discourse about accessibility as it pertains to public, academic and specialized libraries. It is known that the printed and digital media, linked to information and communication technologies (ICTs), can collaborate in the process of knowledge construction of its users, researchers, workers and people with disabilities. In the guidelines of public libraries, management services can contribute to learning throughout the process of human development, facilitating access to and use of information. For the research environment to meet its users needs and expectations, available sources must be clear, with an adequate interface, usability, satisfactory interactivity, and easy accessibility. As for content, the information must be qualitative, pertinent and relevant. In view of the above, we seek to answer the following question: How does interactive communication in public, academic and specialized libraries contribute to ensure that people with disabilities have access to the cognitive capital available in their mediatic environments? The subject of this research is the relationship between interactive media and accessibility to the process of social inclusion in public libraries, using comparative cases between several public, university and specialized libraries as fundamental examples. This research investigated the hypothesis that access through physical and mediatic environments is often not possible, or only partially meets special needs, because such environments are inadequate. A possible gap between the means of communication could further hinder this access and the transmission of information. Therefore, such gaps must be overcome, so that it is possible to pass from a real environment the ideal one in terms of accessibility. To underpin my arguments, the following authors will be cited: Lucia Sfez (1990), Luís Milanesi (1991), Paul Virilio (1993), David Harvey (1994), Eduardo Moresi (2000), Pierre Lévy (2000), Jennifer Rowley (2002), Maria Borges (2003), Yves Le Coadic (2004), McLuhan (2005), García Lopez (2007); Eugênio Trivinho (2007), Néstor Canclini (2008), Silvana Cambiaghi (2008) and João Ribas (2011), among others. This work enabled an understanding of the environmental, informational and technological variables that interfere in the access of people with disabilities to information they seek for their cultural and vocational education, in order to generate knowledge and gain insights about themselves and to transmit them to others